Hypomelanosis of Ito with trisomy 13 mosaicism [46, XY, der (13;13) (q10;q10), +13/46,XY] - Yakıncı, Cengiz; Kutlu, Nurettin Onur; Alp, M. Nail; Şenol, Mustafa; Durmaz, Yaşar; Budak, Turgay (The Turkish Journal of Pediatrics, 2002)
The term hypomelanosis of Ito (HI) has been used as a diagnosis for individuals with swirly hypopigmentation or depigmentation distributed along the lines of Blaschko. HI should be appropriately evaluated for a possible association with chromosomal or genetic mosaicism or chimerism. We report a six-month-old severely motor and mental retarded boy with these typical cutaneous lesions associated with extracutaneous features, including facial dysmorphism, polydactyly, and inguinal hernia. The cytogenetic examination of lymphocytes demonstrated a mosaicism of 46, XY, der (13;13) (q10;q10), +13/46, XY. This is the first case reported in the literature showing an association between phylloid pigmentary pattern of hypomelanosis of Ito and trisomy 13 mosaicism.